Calcium Elevation in Astrocytes Causes an NMDA Receptor-Dependent Increase in the Frequency of Miniature Synaptic Currents in Cultured Hippocampal Neurons - Araque, Alfonso (J Neurosci, 1998)
Astrocytes exhibit a form of excitability and communication on the basis of intracellular Ca(2+) variations (Cornell-Bell et al., 1990; Charles et al., 1991) that can be initiated by neuronal activity (Dani et al., 1992; Porter and McCarthy, 1996). A Ca(2+) elevation in astrocytes induces the release of glutamate (Parpura et al., 1994; Pasti et al., 1997; Araque et al., 1998; Bezzi et al., 1998), which evokes a slow inward current in neurons and modulates action potential-evoked synaptic transmission between cultured hippocampal cells (Araque et al., 1998), suggesting that astrocytes and neurons may function as a network with bidirectional communication. Here we show that a Ca(2+) elevation in astrocytes increases the frequency of excitatory as well as inhibitory miniature postsynaptic currents (mPSCs), without modifying their amplitudes. Thapsigargin incubation, microinjection of the Ca(2+) chelator BAPTA, and photolysis of the Ca(2+) cage NP-EGTA demonstrate that a Ca(2+) elevation in astrocytes is both necessary and sufficient to modulate spontaneous transmitter release. This Ca(2+)-dependent release of glutamate from astrocytes enhances mPSC frequency by acting on NMDA glutamate receptors, because it is antagonized by d-2-amino-5-phosphonopentanoic acid (AP5) or extracellular Mg(2+). These NMDA receptors are located extrasynaptically, because blockage specifically of synaptic NMDA receptors by synaptic activation in the presence of the open channel blocker MK-801 did not impair the AP5-sensitive astrocyte-induced increase of mPSC frequency. Therefore, astrocytes modulate spontaneous excitatory and inhibitory synaptic transmission by increasing the probability of transmitter release via the activation of NMDA receptors.